Poster selection reviewer and curator - Zantides, Evripides (My University, 2026)
The 6th Emirates International Poster Festival (EIPF) has seen exceptional participation, with over 340 designers from 65 countries contributing innovative works under the theme “AI Futures: Creativity Meets Technology.” This remarkable response highlights the global design community’s commitment to exploring AI’s impact on creativity and visual communication.